2006
DOI: 10.1017/s1431927606060156
|View full text |Cite
|
Sign up to set email alerts
|

Vector Piezoresponse Force Microscopy

Abstract: A novel approach for nanoscale imaging and characterization of the orientation dependence of electromechanical properties-vector piezoresponse force microscopy~Vector PFM!-is described. The relationship between local electromechanical response, polarization, piezoelectric constants, and crystallographic orientation is analyzed in detail. The image formation mechanism in vector PFM is discussed. Conditions for complete three-dimensional~3D! reconstruction of the electromechanical response vector and evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
202
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 35 publications
3
202
0
Order By: Relevance
“…17,18,19 Imaging ferroelectric materials in the vicinity of a phase transition at small probing biases or imaging of biological systems with weak electromechanical coupling require optimal imaging conditions to be established, and a number of approaches based on using contact resonances in PFM have been suggested. 20,21 Finally, it is recognized that the use of the cantilever coupled with a beam-deflection detection system typical for most commercial AFM s does not allow longitudinal and normal force components to be unambiguously distinguished, 12,22 and it has been suggested that operation at specific frequencies would allow these components to be differentiated. 22 In our previous publications, we presented in-depth analysis of the static (low frequency) PFM imaging mechanism and demonstrated approaches for data interpretation and visualization.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,19 Imaging ferroelectric materials in the vicinity of a phase transition at small probing biases or imaging of biological systems with weak electromechanical coupling require optimal imaging conditions to be established, and a number of approaches based on using contact resonances in PFM have been suggested. 20,21 Finally, it is recognized that the use of the cantilever coupled with a beam-deflection detection system typical for most commercial AFM s does not allow longitudinal and normal force components to be unambiguously distinguished, 12,22 and it has been suggested that operation at specific frequencies would allow these components to be differentiated. 22 In our previous publications, we presented in-depth analysis of the static (low frequency) PFM imaging mechanism and demonstrated approaches for data interpretation and visualization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the vortex-type domains represent non-steady polarization state with the in-plane components appearing only during dynamic switching. Second, during PFM measurements through the top electrodes, the lateral PFM signal is inevitably affected by the contribution of d 31 and d 32 constants of the piezoelectric tensor of tetragonal PZT, which makes unambiguous detection of the in-plane polarization difficult [17].…”
mentioning
confidence: 99%
“…Vertical PFM ͑VPFM͒ measurements were performed at frequencies 50-100 kHz, which minimizes the longitudinal contribution to measured vertical signal. 12 For lateral PFM ͑LPFM͒, the optimal conditions for contrast transfer were Ïł10 kHz; for higher frequencies, the onset of sliding friction minimizes in-plane oscillation transfer between the tip and the surface. Custom LABVIEW software was developed for simultaneous acquisition of VPFM and LPFM phase and amplitude data, emulating additional SPM data acquisitions channels.…”
mentioning
confidence: 99%